Using Q Methodology in Agricultural Communications Research: A Philosophical Study - Holli R. Leggette; Tobin Redwine (Journal of Applied Communications, 2016)
Communication rests on human experience and the uniqueness of subjectivity. Varying research methods and designs measure subjectivity, but few measure subjectivity using rigorous statistical analysis. Q methodology offers such design and rigor. Yet, agricultural communications has been slow to adopt Q methodology. Therefore, the purpose of this philosophical study was to establish a contextual and philosophical understanding of Q methodology and articulate its uses in agricultural communications research. This philosophical study was without traditional research design and methods. Thus, knowledge gained from the literature and best practices were synthesized with the intent of creating a discussion of the philosophies, concepts, and application of Q methodology. To conduct human subjectivity research, Stephenson proposed Q-methodology. It uses a small number of participants to represent the variance of perspectives about a topic. By focusing on and capturing the holistic perspectives of participants, knowledge bases and understandings of humanistic elements within agricultural communications could be enhanced. Benefits of Q methodology include harnessing subjectivity as a means for testing ideas and characterizing perspectives about an idea, limiting researcher bias, and gaining meaningful data from fewer participants. Challenges include misconceptions and misinterpretations related to terminology, concourse development, and generalizability. Agricultural communications depends on human experience and subjectivity related to food and fiber production. Thus, implementing Q methodology research into the agricultural communications discipline diversifies the research toolbox and provides researchers and practitioners with opportunities to explore perspectives related to diverse agricultural issues.
Keywords: Human Subjectivity; Q Methodology; Research Methods